Climate change and food security in Pacific Island countries (FAO RomeIT, 2008)
Addresses food security and poverty reduction in the face of climate change and energy scarcity. Attempts to the fore food security threats associated with climate change in the food production and supply environments, as well as the broader livelihood and ecological changes that will occur as a consequence.
Keywords: FOOD SECURITY